Probiotic Bacillus amyloliquefaciens SC06 Induces Autophagy to Protect against Pathogens in Macrophages - Wu, Yanping; Wang, Yang; Zou, Hai; Wang, Baikui; Sun, Qiming; Fu, Aikun; Wang, Yuanyuan; Wang, Yibing; Xu, Xiaogang; Li, Weifen (Frontiers in Microbiology, 2017)
Probiotics are increasingly applied in popularity in both humans and animals. Decades of research has revealed their beneficial effects, including the immune modulation in intestinal pathogens inhibition. Autophagy—a cellular process that involves the delivery of cytoplasmic proteins and organelles to the lysosome for degradation and recirculation— is essential to protect cells against bacterial pathogens. However, the mechanism of probiotics-mediated autophagy and its role in the elimination of pathogens are still unknown. Here, we evaluated Bacillus amyloliquefaciens SC06 (Ba)-induced autophagy and its antibacterial activity against Escherichia coli in RAW264.7 cells. Western blotting and confocal laser scanning analysis showed that Ba stimulated autophagy in a dose- and time-dependent manner. Ba-induced autophagy was found to play a role in the elimination of intracellular bacteria when RAW264.7 cells were challenged with Escherichia coli (E.coli). Ba induced autophagy by increasing the expression of Beclin1 and Atg5-Atg12-Atg16 complex, but not the AKT/mTOR signaling pathway. Moreover, Ba pretreatment attenuated the activation of JNK in RAW264.7 cells during E.coli infection, further indicating a protective role for probiotics via modulating macrophage immunity. The above ﬁndings highlight a novel mechanism underlying the antibacterial activity of probiotics. This study enriches the current knowledge on probiotic-mediated autophagy, and provides a new perspective on the prevention of bacterial infection in intestine, which further the application of probiotics in food products.